Analyzing Top 4 Songs of Arctic Monkeys Using Leech’s Morphological and Semantic Deviations - Hana Olivia Marpaung; Yessi Sherly Abigail Ambarita; Alya Saqinah; Uswatun Rafi’a Pasaribu; Rahmadsyah Rangkuti (Lembaga Pengembangan Kinerja Dosen, 2025)
This study describes the morpho-stylistic and the semantic-stylistic features used in the top four songs of Arctic Monkeys’ AM album, namely, “I Wanna Be Yours,” “Do I Wanna Know?”, “Why’d You Only Call Me When You’re High?” and “No. 1 Party Anthem.” This research conducted using a qualitative descriptive method derived from the linguistic deviation theory by Leech analyses of the lyrical texts for their morphological and semantic deviations like informal contractions, neologism, objectification, metaphors and irony. Taking language out of the box, the findings show that Arctic Monkeys have consistently broken linguistic norms in order to produce emotionality, stylistic nuance and lyrical uniqueness. These deviations greatly enhance the band’s lyrical identity of poetic and aesthetic qualities.